(untitled) (Journal of Economic Research & Business Administration, 2016)
This article discusses the types of averages and performance variations. The average value is a general indicator of a statistical population, which repays the individual differences of values of statistical variables, allowing to compare different set of each other. Average always summarizes quantitative trait variation, ie, in the mean values individual differences redeemed units of population due to fortuitous circumstances. In contrast, the average absolute value of characterizing the level of feature separate units together, does not allow to compare the characteristic value in units belonging to different aggregates. So, if you want to compare the levels of compensation of employees at the two companies, it can not be compared on the basis of two employees of different companies. Compensation of employees selected for comparison may not be typical for these enterprises. If we compare the size of the fund pay for the enterprise in question, it does not take into account the number of employees and, therefore, can not determine where the wage level above. In the end, we can only compare the average, ie, as the average worker receives at each facility.